COMPARATIVE EFFECTS OF THREE INSTRUCTIONAL METHODS ON STUDENTS’ PERFORMANCE IN BUILDING TECHNOLOGY IN NIGERIAN POLYTECHNICS - Oviawe, Jane Itohan; Ezeji, S.C.O.A.; Uwameiye, Raymond (European Scientific Journal, ESJ, 2015)
This study investigated the effects of reciprocal peer tutoring, peer tutoring and conventional teaching method on students’ performance in Building Technology using the quasi-experimental research design. The population consisted of all the 232 ND II Building Technology students’ in the four public Polytechnics in Edo, Delta and Ondo States of Nigeria, while the sample comprised of 193 ND II students purposively selected from three out of the three Polytechnics. The instrument used for data collection was the Building Technology Achievement Test (BTAT) which consisted 80 multiple choice items. Three hypotheses guided this study. Data collected were analyzed using Mean and t-test and ANOVA. The findings revealed among others: a significant difference between the Mean post-test score of students RPT and those exposed to CTM, in favour of RPT; Gender had no significant effects on students’ performance; and there was no significant interaction effect of gender and teaching methods on students’ performance. It was recommended among others that: Building Technology teachers should be encouraged to employ RPT more in their teaching in order to increase the level of students’ performance in Building Technology.